Reproductive Ecology of Picea Mariana (Mill.) BSP., at Tree Line Near Inuvik, Northwest Territories, Canada - Black, R. Alan; Bliss, L. C. (Ecological Monographs, 1980)
Picea mariana predominates in even—aged stands of fire origin at the forest—tundra ecotone near Inuvik, Northwest Territories, Canada. Growth rates of P. mariana decrease with increasing latitude and density although growth rates do not change significantly along the ecotone. Field measurements of water relations, when compared with laboratory determinations of leaf water potentials vs. net photosynthesis, suggest no water stress related photosynthetic reduction for mature trees during 1976. Maximum and minimum leaf water potentials for mature trees were —0.6 and —2.1 MPa on 4 August and 1 July, respectively. Winter measurements of water relations also suggest no water stress. In contrast, 1st—yr seedlings demonstrated sensitivity to water stress with high rates of mortality at low levels of water loss. A macro—mesoclimatic gradient of 4°C was found across the tree line (135—km study transect). Picea mariana seed production and germination are limited by this environmental gradient to °40 km south of modern forest line. Germination and survivorship are also affected by microenvironments within a well—developed soil hummock terrain. The lower cardinal germination temperature of 15°C was the determinant of germination timing and success. Seed production estimates suggested little effect on stand reproduction with burn intervals of 100—200 yr. Shorter or longer burn intervals are believed to reduce stand reproduction. Reduced seed longevity, complete stand destruction by wild—fire, and apparent destruction of seed in the soil restrict establishment to 1—8 yr after fire. This may cause local extermination of the species or out—of—equilibrium tree line positions under conditions of deteriorating environment.